Different mechanisms of improving CH3NH3PbI3 perovskite solar cells brought by fluorinated or nitrogen doped graphdiyne - Huang, Huan; Liu, Bing; Wang, Dan; Cui, Rongli; Guo, Xihong; Li, Ying; Zuo, Shouwei; Yin, Zi; Wang, Huanhua; Zhang, Jing; Yuan, Hui; Zheng, Lirong; et al. (Nano research, 2022)
Fluorinated and nitrogen-doped graphdiyne (F/N-GDY) have been used in the active layer of perovskite solar cells (PSCs) for the first time. The introduction of heteroatoms turns out to be an effective method for boosted solar cells performance, which increases by 32.8% and 33.0%, better than the pristine or GDY doped PSCs. The enhanced performance can be attributed firstly to the superiority of F/N-GDY originated from the unique structure and optoelectronic properties of GDY. Then, both can further reduce surface defects and improve surface and bulk crystallinity than pristine GDY. What’s more, efficiency increase caused by F-GDY is mainly attributed to the improvement of fill factor (FF), while the higher short-circuit current ( J SC ) plays more important role by N-GDY doping. Most importantly, the detailed mechanism brought about by doping of F-GDY or N-GDY is expounded by systematical characterizations, especially the synchrotron radiation technique. Doping of F-GDY causes Pb II+ x and forms new Pb-F bonds between F-GDY and Pb ions. Doping of N-GDY or GDY brings about Pb II− x (N-GDY doping induces more deviation than that of GDY due to the participation of imine N), improving its electron density and conductivity.